Penerapan Nilai Al-‘Adālah dalam Good Governance Islam dalam Menjawab Tantangan Keadilan Pemerintah Modern: Analisis Konseptual Atas Integrasi Nilai Keadilan Islam dalam Tata Kelola Pemerintahan Kontemporer - Tabansa, Claudya Vanessa; Aprilya, Denta Nia; Nyoman, Tania Nesa; Adisty, Fadia Ardian; Debataraja, Agnes Tio Evelyna; Baidhowi, Baidhowi (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
The purpose of this study was to examine the relevance and application of the value of al-‘adālah (justice) in building good governance from an Islamic perspective amid the challenges of modern governance. Using a qualitative approach through library research, the study explores the concept of al-‘adālah, the principles of good governance, and their application in contemporary governmental contexts. The findings show that al-‘adālah aligns with good governance principles such as justice, accountability, transparency, participation, and public responsibility. Integrating these values can strengthen the moral and spiritual legitimacy of the bureaucracy while reducing practices of corruption, collusion, and nepotism. In a pluralistic and secular state like Indonesia, good governance based on Islamic values can still be implemented inclusively by emphasizing public ethics and social welfare, making the revitalization of al-‘adālah essential for improving governance.